2019
DOI: 10.1038/s41598-019-56034-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered visual feedback from an embodied avatar unconsciously influences movement amplitude and muscle activity

Abstract: Evidence suggests that the sense of the position of our body parts can be surreptitiously deceived, for instance through illusory visual inputs. However, whether altered visual feedback during limb movement can induce substantial unconscious motor and muscular adjustments is not known. To address this question, we covertly manipulated virtual body movements in immersive virtual reality. Participants were instructed to flex their elbow to 90° while tensing an elastic band, as their virtual arm reproduced the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…Our experience is that participants with a high level of proprioceptive acuity, such as gymnasts, yoga practitioners, and elite-level athletes, find it more difficult to embody a virtual body. We speculate that their intense training results in their brain giving a comparatively greater predictive weighting to proprioceptive input, so that they rely less on the visual input given by the HMD when attempting to produce a prediction regarding their body's spatial location (Bourdin et al, 2019). It is also our experience that embodiment levels, as measured by questionnaire, seem to be lower in more elderly patients.…”
Section: Groups With Reduced Susceptibility To Embodiment Illusionsmentioning
confidence: 82%
See 2 more Smart Citations
“…Our experience is that participants with a high level of proprioceptive acuity, such as gymnasts, yoga practitioners, and elite-level athletes, find it more difficult to embody a virtual body. We speculate that their intense training results in their brain giving a comparatively greater predictive weighting to proprioceptive input, so that they rely less on the visual input given by the HMD when attempting to produce a prediction regarding their body's spatial location (Bourdin et al, 2019). It is also our experience that embodiment levels, as measured by questionnaire, seem to be lower in more elderly patients.…”
Section: Groups With Reduced Susceptibility To Embodiment Illusionsmentioning
confidence: 82%
“…From a predictive processing perspective (Clark, 2016), when inducing a sense of embodiment the precision weighting accorded to vision is higher than for other sensations such as proprioception (Bourdin et al, 2019), touch (Slater et al, 2008) or temperature (Llobera et al, 2013). However, it seems that when there is at least one other form of congruent sensory input, the embodiment illusion is significantly more powerful than with vision alone (Botvinick and Cohen, 1998;Azañón et al, 2016;Marasco, 2018), with visuomotor congruence seemingly more powerful than visuotactile (Kokkinara and Slater, 2014).…”
Section: Challenges To the Sense Of Embodimentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as discussed in the introduction, it has been shown that, in the IVR, ownership can be evoked solely by seeing the virtual body/hand from 1PP, even without the corresponding tactile stimulation 24,25,[28][29][30] , and the 1PP also allows maintaining the feeling of ownership after asynchronous stimulation 56 . In addition, in the IVR setup, unlike the RHI, the participants might not even be aware of the incongruence between the position of their real hand and the virtual hand that they see, again due to the stronger role of vision 32 . Therefore, vision might be given high enough weighting to overcome proprioception and tactile sensations even during asynchronous stimulation, thus evoking a similar proprioceptive drift after Syn and Asyn stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such enhanced role of visual information from the virtual scene can provide ample opportunities for experimental manipulations of body ownership by maintaining the visuo-proprioceptive information constant. For example, it allows creating a mismatch between the movements performed by the virtual and the real body, which the participant remains unaware of 32,33 .…”
mentioning
confidence: 99%